2013
DOI: 10.5271/sjweh.3351
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of carpal tunnel syndrome in US working populations: pooled analysis of six prospective studies

Abstract: Objectives Most studies of carpal tunnel syndrome (CTS) incidence and prevalence among workers have been limited by small sample sizes or restricted to a small subset of jobs. We established a common CTS case definition and then pooled CTS prevalence and incidence data across six prospective studies of musculoskeletal outcomes to measure CTS frequency and allow better studies of etiology. Methods Six research groups collected prospective data at >50 workplaces including symptoms characteristic of CTS and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
212
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(239 citation statements)
references
References 47 publications
5
212
2
9
Order By: Relevance
“…Carpal tunnel syndrome (CTS) is one of the most common musculoskeletal disorders of the upper-extremities (UE-MSD) in working populations (1)(2)(3)(4). As in many industrialized countries, CTS is a leading cause of surgery and occupational diseases (OD) in France (5)(6).…”
mentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is one of the most common musculoskeletal disorders of the upper-extremities (UE-MSD) in working populations (1)(2)(3)(4). As in many industrialized countries, CTS is a leading cause of surgery and occupational diseases (OD) in France (5)(6).…”
mentioning
confidence: 99%
“…By pooling data from six studies that participated in the Upper-Extremity Musculoskeletal Disorder Consortium (UEMSD), Dale et al's recent publication "Prevalence and incidence of carpal tunnel syndrome in US working populations: pooled analysis of six prospective studies" (1) provides an important contribution to the literature on carpal tunnel syndrome (CTS) among US workers. Although the main purpose of the UEMSD was not to estimate the national prevalence of CTS but rather to evaluate the relationship between workplace factors and upper-extremity health outcomes, Dale et al's reported baseline prevalence rate of CTS (7.8%) might be considered one of the best estimates of the true prevalence of CTS among US workers performing hand-intensive activities.…”
Section: What Is the True Prevalence Of Carpal Tunnel Syndrome Among mentioning
confidence: 99%
“…We also found no significant changes in the mean number of CTR and hand fracture cases for residents over the 8-year study period. The literature [12][13][14] shows that the incidence of hand fractures is decreasing, while the rates of carpal tunnel syndrome and CTR are increasing. A recent study 12 of the incidence of CTR in the United States found a decline in CTR in hospital-based surgical centers and a nearly 5-fold increase in CTR performed in freestanding ambulatory surgical centers.…”
Section: Bottom Linementioning
confidence: 99%